Djenné-jeno 1000 years of terracotta statuary in Mali - Grunne, Bernard de (Mercatorfonds, 2014)
Extensive fieldwork in Mali in 1982 led to fascinating discoveries about the function of elegant and sophisticated ancient terracotta sculptures found there as well as their religious and cultural significance. "Jenne-Jeno" investigates this important research and traces potential connections between regions in West Africa whose artistic styles were previously thought to have developed independently. Generously illustrated with hundreds of colour images, this book represents a significant contribution to the study of an art form virtually unknown until a few decades ago. Due to its remarkable soil quality, the uniquely fertile Inland Niger Delta played a crucial role in the development of clay architecture and sculpture in West Africa. The ancient Islamic city of Jenne, located in present-day Sudan, was the first to establish the region's spectacular cylindrical-brick architecture, crafted from the rich earth found there
Keywords: Geschichte 700-1750; Terra-cotta sculpture, Malian / Catalogs; Sculpture, Bambara / Mali / Catalogs; Terra-cotta sculpture, Mandingo / Catalogs; Sculpture, Mandingo / Catalogs; ART / Sculpture; Antiquities; Sculpture, Bambara; Sculpture, Primitive; Terra-cotta sculpture, Malian; Funde; Terrakotta; Inland Niger Delta (Mali) / Antiquities / Catalogs; Mali / Antiquities / Catalogs; Mali; Djenné -- Region; Katalog; Bildband